Magnetorheological Elastomer Stiffness Control for Tunable Vibration Isolator - Gigih Priyandoko; Tedi Kurniawan; Efistein Naga (Proceeding of the Electrical Engineering Computer Science and Informatics, 2018)
Most of the vibration isolator has fixed stiffness such as passive vehicle mounting system. Objective of this research is to develop a Magneto-rheological Elastomer (MRE) as a vibration isolator when different currents are applied to get different stiffness of the MRE. A MRE was fabricated by mixing silicon rubber, silicon oil and carbonyl iron particles together and then cured for 24 hours in a circular mold. Experimental result shows that that there were decreases in amplitude of the vibration in time and frequency domains when the current applied to the coil is increased.